Linguistic Landscape in Kualanamu International Airport - Pasaribu, Gumarpi Rahis; Salmiah, Maryati; Junaidi (Talenta Publisher, 2024)
This paper examines the spread of written language in the public space at Kualanamu International Airport. Kualanamu International Airport is one of the public spaces where members of the public gather together, interact, and communicate. The method used in this research is the descriptive qualitative method. This type of qualitative descriptive research is a research method that utilizes qualitative data and is described in descriptive history. Data for this study were taken from written language related to the Linguistic Landscape at Kualanamu Airport. The study was conducted from the perspective of a linguistic landscape approach. The study results show that language in public spaces is very dynamic and has a variety of designs. Regarding the use of signs, speech spread in public areas combines lingual and non-lingual forms with an attractive design and layout. In terms of function, written language in public spaces on display at Kualanamu Airport is a medium to inform the public.